Highly Porous Tungsten for Plasma-Facing Applications in Nuclear Fusion Power Plants: A Computational Analysis of Hollow Nanoparticles - (:unkn) unknown (IOP PUBLISHING LTD, 2020)
Plasma-facing materials (PFMs) for nuclear fusion, either in inertial confinement fusion (ICF) or in magnetic confinement fusion (MCF) approaches, must withstand extremely hostile irradiation conditions. Mitigation strategies are plausible in some cases, but usually the best, or even the only, solution for feasible plant designs is to rely on PFMs able to tolerate these irradiation conditions. Unfortunately, many studies report a lack of appropriate materials that have a good thermomechanical response and are not prone to deterioration by means of irradiation damage. The most deleterious effects are vacancy clustering and the retention of light species, as is the case for tungsten. In an attempt to find new radiation-resistant materials, we studied tungsten hollow nanoparticles under different irradiation scenarios that mimic ICF and MCF conditions. By means of classical molecular dynamics, we determined that these particles can resist astonishingly high temperatures (up to similar to 3000 K) and huge internal pressures (>5 GPa at 3000 K) before rupture. In addition, in the case of gentle pressure increase (ICF scenarios), a self-healing mechanism leads to the formation of an opening through which gas atoms are able to escape. The opening disappears as the pressure drops, restoring the original particle. Regarding radiation damage, object kinetic Monte Carlo simulations show an additional self-healing mechanism. At the temperatures of interest, defects (including clusters) easily reach the nanoparticle surface and disappear, which makes the hollow nanoparticles promising for ICF designs. The situation is less promising for MCF because the huge ion densities expected at the surface of PFMs lead to inevitable particle rupture.